Application of Composite Deflecting Model in Horizontal Well Drilling. (9th March 2020) - Liu, Shaohu; Zhu, Zhichao
Abstract : Based on current issues of difficulties in controlling horizontal well trajectory and high cost in drilling deflecting, a compound deflecting BHA (bottom hole assembly) with diameter-adjustable stabilizer (DAS) and bending-adjustable housing (BAH) is presented. According to the DAS operational principles and the stress condition in operation, the computational formula of wedge's axial moving displacement and piston's radial telescopic displacement of the DAS driven by drilling fluid pressure is presented. This formula is verified by lab experimental simulation. Three-points-circle method is utilized to calculate geometrical build up rate of compound deflecting BHA, and the result is verified by field data. The method is utilized to make design and calculate for compound BHA. The research can be used as a reference for compound deflecting drilling in horizontal wells. The flow rate and pressure difference have a very serious impact on the flow regulator erosion, so the flow rate and pressure difference should be controlled when the DAS works, and it is suggested that the flow regulator should maintain and replace frequently when in service.